Expanding the phenotype of 12q21 deletions: A role of BTG1 in speech development? - Blum, Katalin; Krumbiegel, Mandy; Kraus, Cornelia; Reis, André; Hüffmeier, Ulrike (European Journal of Medical Genetics, 2023)
We report on a female individual with feeding difficulties, constipation, poor overall growth, periventricular lesions resembling gliosis in brain MRI, recurrent otitis media with palsy of facial nerve, distinct facial features, and pronounced delay in speech development. The latter was the most prominent feature. Molecular karyotyping revealed a heterozygous de novo deletion of 4.353 Mb at chromosome 12q21.33q22. This report expands the number of described individuals with heterozygous deletions at 12q21.33, their clinical spectrum and highlights the clinical variability, even in individuals with deletion of the same genes. Furthermore, our findings indicate a role of BTG1 (OMIM *109580) in speech development.
CRIS-Team Scopus Importer:2023-02-24
Keywords: 12q21.33; Microdeletion; Speech developmental delay